Percutaneous Retrieval of Left Atrial Appendage Closure Devices in Patients With Atrial Fibrillation: A Case Report - Wang, Saihua; Zhang, Juhua; Hao, Shuwen; Zhu, Luoning; Ning, Zhongping; Zhao, Zhihong (Frontiers in Cardiovascular Medicine, 2022)
Left atrial appendage closure (LAAC) devices can be inadvertently released into unfavorable locations, which may allow them to migrate to a different position within the left atrial appendage or embolize from the heart into the aorta. In such instances, it can be challenging to remove the LAAC device. Here, we present two cases in which atrial fibrillation patients experienced LAAC device exposure at an inappropriate site because of interventional operator error and device mismatch, a) LAAC device was dislodged into the aortic arch and retrieved percutaneously form femoral artery route and b) in se left atrium, which was dislodged into the left atrium and retrieved via atrial transseptal puncture of the femoral vein.